THE ROLE OF “MY VILLAGE MY HOME” IN THE KNOWLEDGE AND ATTITUDES OF INTEGRATED HEALTH POST CADRES AND MOTHERS - Anasiya Nurwitasari; Fariani Syahrul; Hario Megatsari; Ratna Dwi Wulandari; Arief Hargono; Djazuli Chalidyanto; Yashwant Vishnupant Pathak (Jurnal Berkala Epidemiologi, 2020)
Background: The percentage infants with complete basic immunization is still below the minimum target of immunization coverage. The immunization coverage survey showed that complete basic immunization and valid dose immunization status in Surabaya City is still below the international averages. Purpose: The purpose of the study was to describe the knowledge and attitudes of cadres and mothers with under two years child (Baduta) towards My Village My Home (MVMH) in the City of Surabaya, Indonesia Methods:  Sampling was done by simple random sampling method. Samples were grouped into exposed groups and unexposed groups. The sample comparison was 1: 2. The respondents of the exposed group were 20 cadres and 20 mothers who had received MVMH training. The respondents of the unexposed group were 40 cadres and 40 mothers who did not receive training. Data collection was done using interviews. The study was conducted in 30 Health Centers. Results: Most cadres in the group who had received training or had not received training had good knowledge, but in the group that had not received training there were 5% of cadres who had poor knowledge. Both mothers in the group of cadres who had received training or had not, had good knowledge, but in the group of cadre that had not received training as much as 10% of mothers had poor knowledge. Both cadres and mothers had a good attitude. Conclusion: Both cadres and mothers in two groups had good knowledge and attitude. Cadres who have good knowledge and attitude towards MVMH have the potential to apply MVMH to the community.